The shape of the journey new and collected poems - Harrison, Jim (Copper Canyon Press, 1998)
This collection includes all of the works from Harrison's eight previous volumes of poetry, including the renowned "Letters to Yesenin, The Theory and Practice of Rivers", and "After Ikkyu", together with new poems. 6 line drawings.
Keywords: Geschichte 1900-2000; American poetry -- 20th century